Comprehensive molecular and phenotypic profiling of uropathogenic Escherichia coli in a Honduran healthcare setting: virulence, resistance and phylogeny - Ortiz, Bryan; Ballesteros-Monrreal, Manuel G.; Galindo, Celeste; Rivera, Daniel; Rivera, Luis; Pérez, Fernando; Maldonado, Victoria; Valle, Elixia; Estrada, Ana; Mendez-Pfeiffer, Pablo; Enríquez, Lourdes; Valencia, Dora; et al. (Frontiers in Microbiology, 2025)
IntroductionUrinary tract infections (UTIs) are a major public health concern, further complicated by the rise of multidrug-resistant bacterial strains. Uropathogenic Escherichia coli (UPEC) is the primary causative agent of UTIs, notable for its genetic diversity and its ability to acquire both virulence and antimicrobial resistance determinants.MethodsThis study conducted a comprehensive phenotypic and molecular characterization of 126 UPEC strains isolated from a tertiary care hospital in Tegucigalpa, Honduras. Seventeen virulence genes were screened, antimicrobial susceptibility to 17 antibiotics was assessed, phylogenetic grouping was performed, and potential clonal relationships were analyzed using ERIC-PCR.ResultsStrains isolated from male patients exhibited significantly higher virulence gene counts (mean: 10.48 vs. 8.06; p = 0.0029), resistance indices (RI = 0.46 vs. 0.27; p < 0.0001), and multidrug resistance rates (88% vs. 63%; p = 0.009) compared to those from female patients. Extended-spectrum β-lactamase (ESBL) production was observed in 42% of isolates, with a higher prevalence in males (59%; p = 0.049). Phylogroup B2 was the most frequent (29%) and was significantly associated with virulence genes papG-II, hlyA, cnf-1, fyuA, and iucD. Despite high genetic heterogeneity observed through ERIC-PCR, clonal clusters sharing similar phylogroups, virulence profiles, and resistance phenotypes were identified. A weak but significant correlation was found between virulence and resistance indices (r = 0.1796; p = 0.0442).DiscussionThis study provides the first in-depth molecular and phenotypic characterization of UPEC in Honduras. The detection of highly virulent and multidrug-resistant strains underscores the need to reinforce local molecular surveillance and to revise empirical treatment guidelines based on local epidemiological data.